Non-Canonical Notch Signaling in Cancer and Immunity - Ayaz, Furkan; Osborne, Barbara A. (Frontiers in Oncology, 2014)
Canonical Notch signaling is initiated by -secretase mediated cleavage of the Notch receptor, leading to the release of the active intra-cellular domain of Notch that migrates to the nucleus and interacts with RBP-J, resulting in the activation of downstream target genes. While canonical Notch signaling is well known to play an active role in several steps during development as well in multiple cell fate decisions, recent evidence from both invertebrate, as well as vertebrate systems, indicate non-canonical, RBP-J independent signaling is important in several cellular processes including oncogenesis and activation of T lymphocytes. These observations raise the possibility that, through an understanding of non-canonical Notch signaling, novel strategies for inhibiting Notch signaling may prove useful in the design of therapies targeted to block aberrant Notch activity. In this mini-review we will examine the current data demonstrating a non-canonical role for Notch signaling in both cancer as well as the immune system and suggest a better understanding of non-canonical signaling may reveal novel strategies to block Notch signaling in disease.